A Solution for Power Crisis and Environment Pollution from Electricity Generation - A Study of Sub-tropical Regions. Issue 1 (2nd January 2021) - Rai, Amit; Shrivastava, Ashish; Jana, Kartick C
ABSTRACT: Air pollution is a primary environmental concern worldwide. The major sources of this pollution are the manufacturing industry, vehicles, diesel generators, and thermal power plants. For limiting this pollution, the resolution is adopted in Paris Climate Agreement to reduce the power dependency on thermal power plants. This work aims to find a solution for phasing out the thermal plant with solar plants for sub-tropical regions of the world. Moreover, the effect of the Air Pollution Index (API) on solar radiation is also predicted with time-series neural network. As a case study, to replace thermal power plant in sub-tropic regions, four metropolitan cities of India are selected. The performance ratio and energy yield of the proposed solar power plants have an average of 76.05% and 1, 167, 447 MWh/year values, respectively, which shows that the proposed power plants are a viable solution to address the aforementioned problem. The potential of the proposed power plant for pollution reduction is also quantified and discussed in detail, and the effect of PM2.5 on solar generation is also reported. Abstract : uf0001